Perceptions On Self-Financed Medical Institutes Among Recent Medical Graduates - Shah, Vinesh; Desai, Kanan T.; Jariwala, Ravi A; Kanpurwala, Danish B; Bansal, RK (National Journal of Community Medicine, 2012)
Background: The issue of high fee payment/Non Residential Indian quota seats and private sector involvement in medical education has drawn a lot of flak from the ethicist in India. Aim: The current study was planned with an aim to explore the perceptions of the recent medical graduates/graduating students of private medical college on self financed medical institutes. Methods: This is a cross-sectional study comprising of personal interviews using a semi-structured questionnaire among 400 recent medical graduates of Surat Municipal Institute of Medical Education and Research. Data analysis was done with help of Epi Info 7. Results: Exactly half 200 (50%) of the respondents were against seeking admission in a self financed institution (Table 1). Almost twice the number of males as compared to females had opined in favor of seeking admission in self financed colleges. Major reason to seek admission in self finance institute given by one third students was that they were clever students who failed to score in their admission examinations, hence has to take admission in the payment medical college. Conclusion: Fresh graduates of private medical institute face a very difficult situation after M.B.B.S, as after years of hard work, they face a gloomy prospect, as a result of a need to recuperate the mammoth amounts of capital invested in private medical colleges.